Analisis Kasus Penyebaran Berita Bohong Terkait Covid-19 di Sumatera Selatan dalam Perspektif Hukum Pidana - Juan Maulana Alfedo (Jurnal Hukum Lex Generalis, 2020)
Advances in technology and information in the modern era have had complex implications in people's lives. In addition to providing ease in accessing information, on the one hand, it also brings negative impacts that can harm individuals, communities, and countries. One of the negative impacts caused is the misuse of electronic media as a means to spread fake news (Hoax). Fake news (Hoax) is an attempt to deceive or outsmart the reader or listener to believe fake news. According to data from the Ministry of Communication and Informatics throughout April 2019, there were 486 cases of hoaxes in Indonesia. One of the cases of fake news (Hoax) that has occurred is the spread of fake news (Hoax) related to Covid-19 in South Sumatra carried out by civil servants (PNS) in one of the Health Centers through posts on social media. As a result of the spread of fake news (Hoax) causes the surrounding community to worry and fear, considering that Covid-19 is a type of virus that has infectious and dangerous properties. In view of the perspective of criminal law, the spread of fake news (Hoax) is one form of criminal acts where the perpetrator can be charged with criminal sanctions in accordance with applicable laws and regulations, namely the Criminal Code (Criminal Code) and Law No. 11 of 2008 Jo. Law No. 19 of 2016 concerning Information and Electronic Transactions.